Remodeling of the gut microbiota and structural shifts in Preeclampsia patients in South China - Liu, J.; Yang, H.; Yin, Z.; Jiang, X.; Zhong, H.; Qiu, D.; Zhu, F.; Li, R. (European journal of clinical microbiology & infectious diseases, 2017)
Preeclampsia (PE) is one of the pregnancy metabolic diseases. Since Gut microbiota play important roles in the hosts’ metabolism, it is necessary to investigate the gut microbiota in PE patients, so that some intestinal dysbiosis might be detected as a biomarker for PE early diagnosis or as a target for intervention. One hundred subjects were categorized into four groups: 26 PE patients in late pregnancy, healthy individuals in early, middle, and late pregnancy (26/24/24 women). Gut microbiota were analyzed by sequencing the V4 region of the 16S rDNA gene using Illuminal MiSeq. Data were analyzed by multivariate statistics. Bacteroidetes was the dominant bacterium (47.57–52.35%) in the pregnant women in South China. Tenericutes increased while Verrucomicrobia almost disappeared in late pregnancy. In the PE patients, there was an overall increase in pathogenic bacteria, Clostridium perfringens ( p = 0.03) and Bulleidia moorei ( p = 0.00) but a reduction in probiotic bacteria Coprococcus catus ( p = 0.03). Our research suggests that there is a significant structural shift of the gut microbiota in PE patients, which might be associated with the occurrence and development of the disease. However, further studies are required to understand the underlying mechanisms.